The three-dimensional life cycle of potential vorticity cutoffs: A global ERA-interim climatology (1979–2017) - Portmann, Raphael; Sprenger, Michael; Wernli, Heini (2020)
The aim of this study is to explore the nature of potential vorticity (PV) cutoff life cycles. While climatological frequencies of such upper-level cyclonic vortices are well known, their life cycle and in particular their three-dimensional evolution is poorly understood. To address this gap, a method is introduced that allows tracking PV cutoffs as three-dimensional objects. As it is based on isentropic air parcel trajectories, the detailed evolution of the cutoffs on isentropic surfaces, including their associated cross-tropopause mass fluxes, can be analyzed. The novel method is applied to the ERA-interim dataset for the years 1979–2017 and the first global climatology of PV cutoffs is presented that is independent of the selection of a vertical level and identifies and tracks PV cutoffs as three-dimensonal features. More than 40 000 PV cutoff life cycles are identified and analyzed in the almost 40-year data set. Known frequency maxima of PV cutoffs are confirmed and, additionally, bands in subtropical areas in the summer hemispheres and a circumpolar band around Antarctica are identified. A detailed investigation of PV cutoff life cycles in different genesis regions reveals that PV cutoff genesis occurs as a result of distinct Rossby wave breaking scenarios. In addition, there is a remarkable regional variability of PV cutoff mobility, lifetimes and vertical evolution. This regional variability of PV cutoff behaviour can to some extent be explained by differences in cross-tropopause mass fluxes and the varying frequencies of different lysis scenarios on isentropic surfaces, i.e. diabatic decay and reabsorption to the stratospheric reservoir. It is found that, on a global average, reabsorption occurs about as frequently as diabatic decay, but on higher isentropic levels. Further, the temporal link between PV cutoffs and associated surface cyclones is investigated. Novel insights are that (i) the frequency and characteristics of this link strongly depend on the region, and (ii) PV cutoffs are frequently involved in surface cyclogenesis a few days after their formation. PV cutoffs forming from similar Rossby wave breaking scenarios in different regions also show remarkable similarities in other characteristics of their life cycle. Based on that, a classification of PV cutoff life cycles into three types is proposed: Type I forms from anticyclonic Rossby wave breaking equatorward of the jet stream, Type II is the result of anticyclonic Rossby wave breaking followed by cyclonic Rossby wave breaking between the polar and the subtropical jets, and Type III forms from cyclonic wave breaking in the storm track regions. While diabatic decay is particularly frequent for Types I and II, reabsorption dominates for the Type III life cycle.